Life and death of the ground sloth Xibalbaonyx oviceps from the Yucatán Peninsula, Mexico - Stinnesbeck, Sarah; Frey, Eberhard; Avilés Olguín, Jerónimo; González, Arturo González; Velázquez Morlet, Adriana; Stinnesbeck, Wolfgang (Historical biology, 2021)
Ongoing investigations in submerged cave systems of Quintana Roo in south-eastern Mexico reveal a rich Late Pleistocene megafaunal assemblage, among them the megalonychid ground sloth Xibalbaonyx oviceps. The taxon has been described based on a complete skull and mandible from El Zapote cenote west of Puerto Morelos. We here add hitherto unreported postcranial material from El Zapote, attributed to the holotype. This new material allows us to reconstruct unexpected locomotion capabilities for Xibalbaonyx oviceps including steep slope and rock climbing. This may have enabled the ground sloth to use the sinkholes and underground caverns as water resource and shelter. The Late Pleistocene age of the fossil allows for a co-existence with early human settlers on the Yucatán Peninsula.
Online publiziert: 21. September 2020
Gesehen am 12.09.2025